Vertical integration in the US cable industry - Ayako Suzuki (Osaka University, Institute of Social and Economic Research (ISER), 2006)
Theory shows that vertical integration has contrasting two effects, efficiency and foreclosure effects. This study empirically estimates the relative size of these two effects. Unlike previous studies, I focus on a single vertical merger in order to use a panel dataset, and estimate its average treatment effects on the several market outcomes. The findings suggest that there was a significant efficiency gain from the merger; the merged systems were found to carry affiliated networks more frequently; there was a larger price decrease in the merged markets. On the other hand, there was weak evidence of foreclosure.
Keywords: L10; L22; L40; C14; 330; Vertikale Integration; Kabelfernsehen; USA